MENEROPONG STRATEGI KEBUDAYAAN MELALUI KESADARAN HISTORIS “PANTANG MELUPAKAN LELUHUR” ISLAM WETU TELU - Fitria Yusrifa; Muhammad Faisal Nur Ikhsan; Rusli Akhmad Junaedi; Muhammad Rodinal Khair (Jurnal Filsafat "WISDOM", 2016)
“Pantang Melupakan Leluhur” is one of devotion's action from Islam Wetu Telu's believers in Desa Bayan, Kecamatan Bayan, Kabupaten Lombok Utara, Nusa Tenggara Barat, for the ancestors, as well as the way of life which makes them survive until now. This study was aiming to seek the cultural strategy behind the immortality of the ancestor values and analyze the historical awareness of "Pantang Melupakan Leluhur" Islam Wetu Telu by using philosophical hermeneutics method. The cultural strategy and the historical awareness of Islam Wetu Telu community relies on the feeling of fear and responsibility to what have been achieved and inherited by the past anchestor. The synthesis of spiral and God' destiny indicate that "Pantang Melupakan Leluhur" in the Islam Wetu Telu community is an ideal concept that is suitable with the historical movement of Indonesia which is attached in the identity of Indonesia, Pancasila.